Efektifitas Permainan Ka-Gem dalam Meningkatkan Pengetahuan Mitigasi Bencana pada Anak Kelas 5 SD - Syifa Aryani; Devi Lusiria (Indo Publishing, 2026)
Indonesia, including Padang City, is highly prone to earthquakes, yet disaster mitigation awareness among elementary students remains limited. This study evaluates the effectiveness of Ka-Gem, an educational card game, in enhancing fifth-grade students’ knowledge of disaster mitigation. Employing a quantitative one-group pretest-posttest design, the study involved 20 students from SDN 29 Dadok Tunggul Hitam. Data were collected through tests administered before and after gameplay and analyzed using a paired sample t-test. Findings revealed a significant improvement in students’ understanding (p < 0.001), suggesting that Ka-Gem fosters active, enjoyable, and meaningful learning. The game's interactive format and visual content supported better retention of mitigation strategies. These results highlight the potential of game-based learning as a tool for disaster education in primary schools.